2017
DOI: 10.4067/s0717-95022017000300024
|View full text |Cite
|
Sign up to set email alerts
|

Ethanol Intake and Toxicity: In Search of New Treatments

Abstract: SANDOVAL, C.; VÁSQUEZ, B.; MANDARIM-DE-LACERDA, C. & DEL SOL, M.Ethanol intake and toxicity: In search of new treatments. Int. J. Morphol., 35(3):942-949, 2017. SUMMARY:Prolonged alcohol consumption has consequences on the liver, producing necrotic precipitates and fibrosis, on the pancreas, causing the pancreatic acini to atrophy and destroying insulin-producing cells, and on the central nervous system (CNS), causing the gray and white matter in the frontal lobes of the brain and cerebellum to atrophy. Genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 78 publications
(82 reference statements)
0
9
0
1
Order By: Relevance
“…PAE programming for neurological effects is well researched; however, its role in metabolic programming has not received much attention, especially with alcohol as a second hit. Furthermore, heavy/chronic alcohol consumption in adolescence and young adulthood could result in cardio‐metabolic effects due to the toxic effects of alcohol and its intermediate metabolite, AA (Sandoval, Vásquez, Mandarim‐de‐Lacerda, & Sol, 2017). The harmful impact of alcohol on the cardiometabolic system and its mechanism is described in subsequent sections.…”
Section: Pae and Metabolic Programmingmentioning
confidence: 99%
“…PAE programming for neurological effects is well researched; however, its role in metabolic programming has not received much attention, especially with alcohol as a second hit. Furthermore, heavy/chronic alcohol consumption in adolescence and young adulthood could result in cardio‐metabolic effects due to the toxic effects of alcohol and its intermediate metabolite, AA (Sandoval, Vásquez, Mandarim‐de‐Lacerda, & Sol, 2017). The harmful impact of alcohol on the cardiometabolic system and its mechanism is described in subsequent sections.…”
Section: Pae and Metabolic Programmingmentioning
confidence: 99%
“…[36] In addition, baicalin can alleviate ethanol-induced liver damage in rats, probably due to its antioxidant, anti-inflammatory properties, and the activation of Shh, which plays an important role in the morphogenesis of tissues and liver repair. [15,37] In this sense, in vitro studies on HepG2 cells have shown that SQEA and SQEE80 enhance cellular growth rates. [31,32] While, phytochemicals treatment has shown an increased proliferation on SK-Hep-1 cells.…”
Section: Summary Of Key Findings and Interpretationmentioning
confidence: 99%
“…Hasil penelitian ini berbeda dengan penelitian yang dilakukan oleh (Sandoval et al, 2017). Selain itu kandungan sianida yang berbeda dapat terjadi karena adanya proses pengolahan.…”
Section: Struktur Histopatologi Lambungunclassified